A high-nickel positive electrode material with water washing-induced surface reconstruction, and a preparation method and application thereof

CN122877823APending Publication Date: 2026-10-09GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611335915.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明提供了一种水洗诱导表面重构的高镍正极材料及制备方法和应用,以解决现有水洗方法因表面结构退化导致高镍正极材料容量衰减和循环稳定性差的问题

Benefits of technology

本发明提供的水洗诱导表面重构的高镍正极材料的制备方法,通过在水洗液中加入NH4+盐和H2O2,并将pH值控制在7.5~10.5,利用NH4+的选择性络合作用从高镍正极材料表面亚层中抽取部分Ni2+以形成局域阳离子空位,配合H2O2的氧化作用促进表面Ni2+向Ni3+转化以引导阳离子有序排列,二者协同作用使高镍正极材料表面在去除残碱的同时进行表面原位重构,解决了传统水洗工艺无法控制表面结构演化方向的问题。在此基础上,本发明通过300℃~600℃的低温热处理使水洗过程中形成的亚稳态重构层结晶有序化并锁定为稳定的功能性结构,该温度低于高镍正极材料本体烧结温度,不会对本体结构产生影响。本发明在充分去除高镍正极材料表面残碱的同时,抑制了晶格锂过度脱出和有害NiO岩盐相的形成,在材料表面构建了具有高离子电导率的功能性重构层,有效兼顾了残碱去除效果和表面结构稳定性,使材料的首次放电容量、首次库伦效率和循环容量保持率均得到明显提升。此外,本发明方法工艺简单,在常规水洗设备上即可实施,成本较低,易于工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877823A_ABST
    Figure CN122877823A_ABST
Patent Text Reader

Abstract

The application provides a high-nickel positive electrode material with water washing induced surface reconstruction, a preparation method and application. + The preparation method comprises the following steps: dispersing sintered high-nickel positive electrode material in a water washing solution containing NH4 The pH value of the water washing solution is 7.5-10.5; after water washing, solid-liquid separation is performed, the solid material is collected and dried; and the dried material is subjected to heat treatment at 300-600 DEG C under an oxygen atmosphere. The preparation method of the high-nickel positive electrode material with water washing induced surface reconstruction can remove residual alkali on the surface of the high-nickel positive electrode material while inducing in-situ reconstruction of the material surface, thereby improving the electrochemical performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery cathode material technology, specifically to a high-nickel cathode material with water-washed induced surface reconstruction, its preparation method, and its application. Background Technology

[0002] High-nickel layered cathode materials have become one of the preferred cathode materials for next-generation high-energy-density lithium-ion batteries due to their specific capacity exceeding 200 mAh / g and relatively low cost. However, residual alkaline lithium compounds such as lithium hydroxide and lithium carbonate easily form on the surface of this material, with residual alkali content typically reaching thousands of ppm. This leads to problems such as slurry gelation, side reactions with the electrolyte to generate gas, and increased interfacial impedance. Water washing is currently the most effective and economical method for removing residual alkali on the surface in industry. However, while traditional deionized water washing removes residual alkali, water molecules undergo ion exchange reactions with near-surface lattice lithium, resulting in the loss of lithium ions from the surface sublayer. This destabilizes the layered structure and induces the formation of an electrochemically inert NiO rock salt phase, significantly increasing interfacial impedance and causing a continuous deterioration in rate performance and cycle stability. Furthermore, there is a contradiction between insufficient alkali removal due to too short a washing time and excessive surface erosion due to too long a washing time.

[0003] To address the aforementioned issues, some improvements have been attempted by adding components such as ammonia, organometallic coating agents, or graphene oxide solutions to the washing solution, aiming to protect the material surface while removing residual alkali. However, these solutions remain focused on mitigating the physical or chemical damage to the surface caused by washing, representing a passive protection mode. They do not address the fundamental issues of water washing leading to the degradation of the material's layered surface structure, repeated regeneration of residual alkali, and exacerbated interfacial side reactions. Consequently, the capacity decay and cycle stability deterioration problems of high-nickel cathode materials remain unresolved. Summary of the Invention

[0004] This invention provides a high-nickel cathode material with water washing-induced surface reconstruction, its preparation method, and its application, in order to solve the problems of capacity decay and poor cycle stability of high-nickel cathode materials caused by surface structure degradation in existing water washing methods.

[0005] In a first aspect, the present invention provides a method for preparing a high-nickel cathode material with water-washed induced surface reconstruction, comprising the following steps: Water washing: The sintered high-nickel cathode material is dispersed in a water washing solution for water washing; wherein the water washing solution contains NH4. + Salt and H2O2, and the pH value of the washing solution is 7.5~10.5; for example, the pH value of the washing solution can be 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, or 10.5. Solid-liquid separation: After water washing, solid-liquid separation is performed to collect the solid material; Drying: The process of drying the collected solid materials; Heat treatment: The dried material is heat-treated at 300℃~600℃ in an oxygen atmosphere. For example, the heat treatment temperature can be 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, or 600℃.

[0006] During the water washing process of this invention, NH4 + With Ni in the surface sublayer 2+ A stable complex [Ni(NH3)] is formed. n ] 2+ (Under specific conditions, the coordination number can be 3 to 6), extracting a portion of Ni from specific lattice sites. 2+ This causes localized cation vacancies and stoichiometric shifts, disrupting the original layered structural equilibrium and providing a thermodynamic driving force for the surface to reconstruct into a spinel phase or an ordered lithium-deficient phase. H₂O₂, as a mild oxidant, promotes the surface Ni… 2+ To Ni 3+ The transformation results in a more uniform and ordered distribution of cation valence states, which is conducive to the formation of an ordered spinel structure. The weakly alkaline environment effectively dissolves and removes surface LiOH and Li₂CO₃, while also inhibiting H₂O. + With Li lattice + The exchange reaction reduces excessive lithium extraction from the lattice, preventing the formation of harmful rock salt phases. NH4 + H2O2 provides the driving force for structural reconstruction, while H2O2 provides the directionality for structural reconstruction. Together, they ensure that the surface is reconstructed towards a beneficial spinel phase or an ordered lithium-deficient phase. Heat treatment further crystallizes and orders the metastable surface reconstruction layer formed during water washing, locking the reconstruction layer into a stable functional structure.

[0007] In this invention, the pH value should be measured at the temperature of the washing solution, and the measurement temperature should be consistent with the washing temperature. Since the pH value changes with temperature, it is recommended to use a precision pH meter with temperature compensation function.

[0008] In one optional embodiment, the pH value of the washing solution is 8.5 to 9.5; And / or, the temperature of the heat treatment is 400℃~500℃.

[0009] In one alternative implementation, the NH4 + The salt includes at least one of ammonium chloride (NH4Cl), ammonium nitrate (NH4NO3), and ammonium sulfate ((NH4)2SO4); NH4Cl, NH4NO3, and (NH4)2SO4 can all achieve the technical effects of this invention. Among them, NH4Cl has the best effect (Cl... - (No side effects on the surface), NH4NO3 is second (NO3) -(It can be decomposed and volatilized during subsequent heat treatment), (NH4)2SO4, and then (SO4). 2- (There may be residue; the rinsing time needs to be extended to ensure it is thoroughly cleaned). And / or, the washing solution contains NH4 + The salt concentration is 0.01 mol / L to 0.5 mol / L; for example, the NH4+. + The salt concentration can be 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or 0.5 mol / L; preferably 0.05 mol / L to 0.2 mol / L. And / or, the mass fraction of H2O2 in the washing solution is 0.1%~5%; the mass fraction of H2O2 in the washing solution can be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 3.0%, 4.0%, 5.0%; preferably 0.5%~2%. H2O2 is easily decomposed under alkaline conditions and at higher temperatures, and the washing solution should be prepared and used immediately. If it needs to be prepared in batches, it should be stored in the dark and at low temperature (4°C) and used up within 24 hours.

[0010] In one optional embodiment, the washing solution further comprises a pH buffer; optionally, the pH buffer comprises ammonia (NH3·H2O) or an NH4Cl-NH3·H2O buffer solution. And / or, the washing solution is prepared by heating deionized water to 25°C~60°C and adding NH4. + Salt and H2O2 are stirred until homogeneous to obtain the washing solution; optionally, the washing solution is prepared by heating deionized water to 35-45°C and adding NH4+. + Salt and H2O2 are stirred evenly to obtain the washing solution. For example, the temperature at which the deionized water is heated can be 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, or 60℃.

[0011] In one optional embodiment, the sintered high-nickel cathode material has the chemical formula LiNi. x Co y M 1-x-y O2, where 0.80 ≤ x ≤ 0.98, 0 < y < 0.20, and x + y < 1, and M is Mn and / or Al. For example, x can be 0.80, 0.85, 0.88, 0.90, 0.95, 0.98; y can be 0.01, 0.05, 0.08, 0.10, 0.15, 0.19. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in each of the stated ranges. Specifically, it includes, but is not limited to: LiNi 0.81 Co0.10 Mn 0.09 O2, LiNi 0.90 Co 0.05 Mn 0.05 O2, LiN 0.90 Co 0.05 Al 0.05 O2, LiNi 0.95 Co 0.02 Al 0.03 For high-nickel materials such as O2, the recommended heat treatment temperature is 400~500℃ for the NCA system and 420~500℃ for the NCM system. Temperatures that are too low (<300℃) will result in incomplete crystallization of the reconstructed layer, while temperatures that are too high (>600℃) may induce secondary changes in the bulk structure. Heat treatment must be carried out in an oxygen atmosphere (purity ≥99.5%) at a flow rate of 50~200 mL / min. If carried out in an air atmosphere, new residual alkali may form on the material surface due to the introduction of moisture and CO2.

[0012] In one optional embodiment, the solid-liquid ratio of the sintered high-nickel cathode material to the washing solution is 1:(1~10)g / mL; for example, the solid-liquid ratio can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, or 1:10; preferably 1:(2~4)g / mL; And / or, the stirring speed during the water washing process is 100 rpm to 800 rpm; for example, the stirring speed can be 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, or 800 rpm; preferably 300 rpm to 500 rpm.

[0013] In one optional embodiment, the temperature of the water washing process is 10°C to 50°C; for example, the temperature of the water washing process can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, or 50°C; preferably 25°C to 40°C. And / or, the water washing treatment time is 1 min to 30 min; for example, the water washing treatment time can be 1 min, 3 min, 5 min, 8 min, 10 min, 15 min, 20 min, 25 min, or 30 min; preferably 3 min to 15 min. The water washing time is related to the material particle size and specific surface area. For large particle materials (D50≈10 μm), a water washing time of 8 to 15 min is recommended. If the water washing time is too short (<1 min), the reconstruction will be insufficient, and if it is too long (>30 min), it may lead to excessive erosion.

[0014] In one optional embodiment, the drying process is vacuum drying at 80℃~150℃ for 2h~12h; for example, the drying temperature can be 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, or 150℃; the drying time can be 2h, 4h, 6h, 8h, 10h, or 12h; for space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in each of the aforementioned ranges. Preferably, the drying process is vacuum drying at 100℃~120℃ for 6h~10h. And / or, the heat treatment holding time is 2h to 10h; the heat treatment holding time can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, or 10h; preferably 4h to 8h; And / or, after the heat treatment is completed, the furnace is cooled to room temperature and then sieved.

[0015] In one optional embodiment, the sintered high-nickel cathode material is obtained by the following method: a high-nickel cathode material precursor is mixed with a lithium source, and then sintered once at 750°C to 900°C for 5 to 15 hours in an oxygen atmosphere to obtain the sintered high-nickel cathode material. Preferably, the sintering is carried out once at 750°C to 820°C for 10 to 12 hours in an oxygen atmosphere.

[0016] In one optional embodiment, the high-nickel cathode material precursor is a hydroxide precursor prepared by co-precipitation, with the chemical formula Ni. x Co y M 1-x-y (OH)2, wherein 0.80≤x≤0.98, 0<y<0.20, and x+y<1, and M is Mn and / or Al; the lithium source is lithium hydroxide (LiOH·H2O).

[0017] In a second aspect, the present invention also provides a high-nickel cathode material with water-wash-induced surface reconstruction, which is prepared by the preparation method of the high-nickel cathode material with water-wash-induced surface reconstruction described in the first aspect.

[0018] Thirdly, the present invention also provides the application of the high-nickel cathode material with water washing-induced surface reconstruction as described in the second aspect in the preparation of lithium-ion battery cathode sheets.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention provides a method for preparing high-nickel cathode materials with water-washed induced surface reconstruction, which involves adding NH4 to the water washing solution. + Salt and H2O2, and control the pH value at 7.5~10.5, utilizing NH4+. +Selective complexation extracts a portion of Ni from the surface sublayer of high-nickel cathode materials. 2+ To form localized cation vacancies, and in conjunction with the oxidation effect of H2O2, promote the surface Ni 2+ To Ni 3+ The conversion guides the ordered arrangement of cations, and the synergistic effect of these two processes enables in-situ surface reconstruction of high-nickel cathode materials while removing residual alkali, solving the problem that traditional water washing processes cannot control the direction of surface structure evolution. Based on this, the present invention uses low-temperature heat treatment at 300℃~600℃ to crystallize and lock the metastable reconstructed layer formed during water washing into a stable functional structure. This temperature is lower than the sintering temperature of the high-nickel cathode material itself and will not affect the bulk structure. The present invention effectively removes residual alkali from the surface of high-nickel cathode materials while suppressing excessive lithium extraction from the lattice and the formation of harmful NiO rock salt phases. It constructs a functional reconstructed layer with high ionic conductivity on the material surface, effectively balancing residual alkali removal and surface structure stability, resulting in a significant improvement in the material's initial discharge capacity, initial coulombic efficiency, and cycle capacity retention. Furthermore, the method of the present invention is simple, can be implemented on conventional water washing equipment, has low cost, and is easy to industrialize. Attached Figure Description

[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0021] Figure 1 This is a comparison chart of the cycling performance of the surface-reconstructed high-nickel materials prepared in Examples 1 to 3 of the present invention and the high-nickel cathode materials prepared in Comparative Examples 1 to 3, under a 1C rate and a voltage range of 2.8 to 4.3V. Detailed Implementation

[0022] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.

[0023] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0024] The main raw materials and equipment used in the following examples are as follows: Deionized water (resistivity ≥18MΩ·cm); NH4Cl (analytical grade, purity ≥99.5%) H2O2 (analytical grade, mass fraction 30%) NH3·H2O (analytical grade, 25% by mass); Thermostatic water bath (temperature control accuracy ±0.5℃); Electric mixer (speed range 0~1000rpm); Vacuum filtration device (equipped with a 0.22μm filter membrane); Vacuum drying oven (temperature control accuracy ±1℃); Tubular atmosphere furnace (equipped with oxygen gas line, temperature control accuracy ±1℃).

[0025] Example 1 This embodiment provides a method for preparing a high-nickel cathode material with water washing-induced surface reconstruction, the specific steps of which are as follows: S1. The 9-series NCA high-nickel cathode material (chemical formula LiNi) after one sintering 0.90 Co 0.05 Al 0.05 O2, D50≈10μm, Ni hydroxide precursor prepared by co-precipitation method 0.90 Co 0.05 Al 0.05 (OH)₂ is mixed with LiOH·H₂O and sintered at 750℃ for 12 hours under an oxygen atmosphere to obtain a solution that is then dispersed in a washing solution for washing. Precautions: H₂O₂ decomposes easily at high temperatures, therefore the temperature of the washing solution should not exceed 60℃; H₂O₂ should be added immediately before use to avoid a decrease in concentration due to prolonged storage; pH adjustment should be performed after adding H₂O₂, as its addition will affect the pH value of the solution.

[0026] S2. The washing solution is prepared by the following method: Take 1000 mL of deionized water, place it in a 2 L beaker, and heat it to 35°C in a constant temperature water bath and maintain the temperature; add NH4Cl to the water to reduce the NH4 content in the washing solution. + The salt concentration is 0.1 mol / L, and it is stirred until completely dissolved; 30% H2O2 solution is added to make the mass fraction of H2O2 in the washing solution 1.0%; the pH is slowly adjusted to 9.0 with NH3·H2O (using a precision pH meter for monitoring), and stirring is continued for 5 minutes until homogeneous to obtain the washing solution with a pH value of 9.0.

[0027] S3. Disperse 100g of the 9-series NCA high-nickel cathode material after one sintering in the prepared water washing solution (solid-liquid ratio of 1g:10mL), stir at 400rpm for 10min in a 35℃ water bath, and perform water washing treatment.

[0028] S4. After washing with water, a vacuum filtration device (equipped with a 0.22μm filter membrane) is used to separate solids and liquids, collect solid materials, and rinse the filter cake twice with about 50mL of deionized water.

[0029] S5. Place the collected solid material in a vacuum drying oven and dry it for 6 hours at 120℃ and a vacuum degree ≤ -0.09MPa.

[0030] S6. Place the dried material in a corundum boat and put it into a tube furnace. Heat the material to 450°C at a heating rate of 2°C / min and hold it at this temperature for 6 hours in an oxygen atmosphere (oxygen flow rate 100 mL / min). After heat treatment, cool the material to room temperature in the furnace (cooling rate approximately 3°C / min). Remove the material and pass it through a 300-mesh sieve to obtain a high-nickel cathode material with water-washed induced surface reconstruction. Precautions: The heat treatment process must be carried out in an oxygen atmosphere to avoid oxygen loss at high temperatures; the heating rate should not be too fast (≤5°C / min recommended) to avoid uneven heating of the material; it is recommended to cool the material in the furnace to avoid thermal stress cracking caused by quenching.

[0031] S7. X-ray diffraction analysis was performed on the high-nickel cathode material prepared in Example 1. The results showed that the material surface had characteristic diffraction peaks belonging to the spinel phase, and the peak positions were consistent with the standard card of spinel structure. High-resolution transmission electron microscopy observation showed that the near-surface region of the material had lattice fringes that were different from the bulk layered structure, and the interplanar spacing was consistent with the characteristic crystal faces of the spinel phase, further indicating that the surface had been reconstructed into a spinel structure in situ.

[0032] Example 2 This embodiment provides a method for preparing a high-nickel cathode material with water washing-induced surface reconstruction, the specific steps of which are as follows: S1. The high-nickel cathode material (chemical formula LiNi) after one sintering 0.81 Co 0.10 Mn 0.09 O2, Ni hydroxide precursor prepared by co-precipitation method 0.81 Co 0.10 Mn 0.09 (OH)2 was mixed with LiOH·H2O and sintered at 750℃ for 12h under an oxygen atmosphere to obtain a solution that was then dispersed in a washing solution for washing.

[0033] S2. The washing solution is prepared by the following method: Take 1000 mL of deionized water and heat it to a constant temperature of 30°C; add (NH4)2SO4 to the water to reduce the NH4 content in the washing solution. + The salt concentration is 0.08 mol / L, and it is stirred until completely dissolved; a 30% H2O2 solution is added to make the mass fraction of H2O2 in the washing solution 0.8%; the pH is adjusted to 9.2 with NH3·H2O, and stirred evenly to obtain the washing solution with a pH value of 9.2.

[0034] S3. Disperse 200g of the high-nickel cathode material after one sintering into the prepared water washing solution (solid-liquid ratio of 1g:2mL), stir at 300rpm for 8min in a 30℃ water bath, and perform water washing treatment.

[0035] S4. After washing with water, vacuum filtration is performed to separate solids and liquids, collect the solid material, and rinse the filter cake twice with about 80 mL of deionized water.

[0036] S5. Place the collected solid material in a vacuum drying oven and dry it for 8 hours at 110℃ and a vacuum degree ≤ -0.09MPa.

[0037] S6. Place the dried material in a tube furnace and heat it to 420°C at a heating rate of 3°C / min. Hold the temperature at this temperature for 8 hours in an oxygen atmosphere (oxygen flow rate 100 mL / min) for heat treatment. After heat treatment, cool the material to room temperature with the furnace, remove the material, and pass it through a 300-mesh sieve to obtain a high-nickel cathode material with water-washed induced surface reconstruction.

[0038] S7. X-ray diffraction (XRD) analysis was performed on the high-nickel cathode material prepared in Example 2. The results showed that the material surface had characteristic diffraction peaks belonging to the spinel phase, and the peak positions were consistent with the standard card of spinel structure. High-resolution transmission electron microscopy observation showed that the near-surface region of the material had lattice fringes that were different from the bulk layered structure, and the interplanar spacing was consistent with the characteristic crystal faces of the spinel phase, further indicating that the surface had been reconstructed into a spinel structure in situ.

[0039] Example 3 This embodiment provides a method for preparing a high-nickel cathode material with water washing-induced surface reconstruction, the specific steps of which are as follows: S1. The high-nickel cathode material (chemical formula LiNi) after one sintering 0.90 Co 0.05 Mn 0.05 O2, Ni hydroxide precursor prepared by co-precipitation method 0.90 Co 0.05 Mn 0.05(OH)2 was mixed with LiOH·H2O and sintered at 750℃ for 12h under an oxygen atmosphere to obtain a solution that was then dispersed in a washing solution for washing.

[0040] S2. The washing solution is prepared by the following method: Take 1000 mL of deionized water and heat it to a constant temperature of 40°C; add NH4NO3 to the water to reduce the NH4 content in the washing solution. + The salt concentration is 0.15 mol / L, and it is stirred until completely dissolved; a 30% H2O2 solution is added to make the mass fraction of H2O2 in the washing solution 1.5%; the pH is adjusted to 8.8 with NH3·H2O, and stirred evenly to obtain the washing solution with a pH value of 8.8.

[0041] S3. Disperse 100g of the high-nickel cathode material after one sintering in the prepared washing solution (solid-liquid ratio of 1g:4mL), and stir at 500rpm for 5min in a 40℃ water bath for washing. Precautions: Avoid generating excessive foam during stirring (a small amount of bubbles may be generated by H2O2 under stirring). If excessive foam is generated, reduce the stirring speed appropriately. The washing time should be started from the time the material is added to the washing solution. Maintain a constant temperature during the washing process.

[0042] S4. After washing, centrifugation (4000 rpm, 5 min) is used to separate solids and liquids and collect solid materials.

[0043] S5. Place the collected solid material in a vacuum drying oven and dry it for 10 hours at 100℃ and a vacuum degree ≤ -0.09MPa.

[0044] S6. Place the dried material in a tube furnace and heat it to 500°C at a heating rate of 4°C / min. Hold the temperature in an oxygen atmosphere (oxygen flow rate 100 mL / min) for 4 hours for heat treatment. After heat treatment, cool the material to room temperature with the furnace, remove the material, and pass it through a 300-mesh sieve to obtain a high-nickel cathode material with water-washed induced surface reconstruction.

[0045] S7. X-ray diffraction (XRD) analysis was performed on the high-nickel cathode material prepared in Example 3. The results showed that the material surface had characteristic diffraction peaks belonging to the spinel phase, and the peak positions were consistent with the standard card of spinel structure. High-resolution transmission electron microscopy observation showed that the near-surface region of the material had lattice fringes that were different from the bulk layered structure, and the interplanar spacing was consistent with the characteristic crystal faces of the spinel phase, further indicating that the surface had been reconstructed into a spinel structure in situ.

[0046] Example 4 This embodiment provides a method for preparing a high-nickel cathode material with water washing-induced surface reconstruction, the specific steps of which are as follows: S1. The high-nickel cathode material (chemical formula LiNi) after one sintering 0.95 Co 0.02 Al 0.03 O2, Ni hydroxide precursor prepared by co-precipitation method 0.95 Co 0.02 Al 0.03 (OH)2 is mixed with LiOH·H2O and sintered at 820℃ for 10h under an oxygen atmosphere to obtain a solution that is then dispersed in a washing solution for washing.

[0047] S2. The washing solution is prepared by the following method: Take 1000 mL of deionized water and heat it to a constant temperature of 35°C; add NH4Cl to the water to reduce the NH4 content in the washing solution. + The salt concentration is 0.05 mol / L, and it is stirred until completely dissolved; a 30% H2O2 solution is added to make the mass fraction of H2O2 in the washing solution 0.5%; the pH is adjusted to 7.5 with NH3·H2O, and stirred evenly to obtain the washing solution with a pH value of 7.5.

[0048] S3. Disperse 200g of the high-nickel cathode material after one sintering into the prepared water washing solution (solid-liquid ratio of 1g:4mL), stir at 300rpm for 15min in a 50℃ water bath, and perform water washing treatment.

[0049] S4. After washing with water, vacuum filtration is performed to separate solids and liquids, collect the solid material, and rinse the filter cake twice with about 100 mL of deionized water.

[0050] S5. Place the collected solid material in a vacuum drying oven and dry it for 6 hours at 120℃ and a vacuum degree ≤ -0.09MPa.

[0051] S6. Place the dried material in a tube furnace and heat it to 300°C at a heating rate of 1°C / min. Hold the temperature at this temperature for 8 hours in an oxygen atmosphere (oxygen flow rate 50 mL / min) for heat treatment. After heat treatment, cool the material to room temperature with the furnace, remove the material, and pass it through a 325-mesh sieve to obtain a high-nickel cathode material with water-washed induced surface reconstruction.

[0052] S7. X-ray diffraction (XRD) analysis was performed on the high-nickel cathode material prepared in Example 4. The results showed that the material surface had characteristic diffraction peaks belonging to the spinel phase, and the peak positions were consistent with the standard card of spinel structure. High-resolution transmission electron microscopy observation showed that the near-surface region of the material had lattice fringes that were different from the bulk layered structure, and the interplanar spacing was consistent with the characteristic crystal faces of the spinel phase, further indicating that the surface had been reconstructed into a spinel structure in situ.

[0053] Example 5 This embodiment provides a method for preparing a high-nickel cathode material with water washing-induced surface reconstruction, the specific steps of which are as follows: S1. The high-nickel cathode material (chemical formula LiNi) after one sintering 0.85 Co 0.10 Mn 0.05 O2, Ni hydroxide precursor prepared by co-precipitation method 0.85 Co 0.10 Mn 0.05 (OH)2 was mixed with LiOH·H2O and sintered at 750℃ for 12h under an oxygen atmosphere to obtain a solution that was then dispersed in a washing solution for washing.

[0054] S2. The washing solution is prepared by the following method: Take 1000 mL of deionized water and heat it to a constant temperature of 45°C; add NH4NO3 to the water to reduce the NH4 content in the washing solution. + The salt concentration is 0.2 mol / L, and it is stirred until completely dissolved; a 30% H2O2 solution is added to make the mass fraction of H2O2 in the washing solution 2.0%; the pH is adjusted to 10.5 with NH4Cl-NH3·H2O buffer solution, and stirred evenly to obtain the washing solution with a pH value of 10.5.

[0055] S3. Disperse 100g of the high-nickel cathode material after one sintering into the prepared water washing solution (solid-liquid ratio of 1g:2mL), stir at 500rpm for 3min in a 10℃ water bath, and perform water washing treatment.

[0056] S4. After washing, centrifugation (4000 rpm, 5 min) is used to separate solids and liquids and collect solid materials.

[0057] S5. Place the collected solid material in a vacuum drying oven and dry it for 10 hours at 100℃ and a vacuum degree ≤ -0.09MPa.

[0058] S6. Place the dried material in a tube furnace and heat it to 600°C at a heating rate of 5°C / min. Hold the temperature at this temperature for 4 hours in an oxygen atmosphere (oxygen flow rate 200 mL / min) for heat treatment. After heat treatment, cool the material to room temperature with the furnace, remove the material, and pass it through a 400-mesh sieve to obtain a high-nickel cathode material with water-washed induced surface reconstruction.

[0059] S7. X-ray diffraction (XRD) analysis was performed on the high-nickel cathode material prepared in Example 5. The results showed that the material surface had characteristic diffraction peaks belonging to the spinel phase, and the peak positions were consistent with the standard card of spinel structure. High-resolution transmission electron microscopy observation showed that the near-surface region of the material had lattice fringes that were different from the bulk layered structure, and the interplanar spacing was consistent with the characteristic crystal faces of the spinel phase, further indicating that the surface had been reconstructed into a spinel structure in situ.

[0060] Comparative Example 1 This comparative example provides a method for preparing a high-nickel cathode material using conventional pure water washing, which differs from Example 1 in that the washing solution is deionized water and does not contain NH4. + Salt and H2O2; other conditions are the same as in Example 1.

[0061] Comparative Example 2 This comparative example provides a water washing treatment method for high-nickel cathode materials, which differs from Example 1 in that the water washing solution does not contain H2O2; other conditions are the same as in Example 1.

[0062] Comparative Example 3 This comparative example provides a water washing treatment method for high-nickel cathode materials, which differs from Example 1 in that the water washing solution does not contain NH4. + Salt; other conditions are the same as in Example 1.

[0063] Test Example 1 The surface residual alkali content and electrochemical performance of the high-nickel cathode materials prepared in Examples 1-5 and Comparative Examples 1-3 were tested.

[0064] Surface residual alkali content test: The LiOH and Li2CO3 content on the surface of the high-nickel cathode materials prepared in each example and comparative example was determined by potentiometric titration. The test results are shown in Table 1.

[0065] Electrochemical performance testing: The high-nickel cathode materials prepared in each example and comparative example were mixed with polyvinylidene fluoride (PVDF) and acetylene black at a mass ratio of 90:5:5, respectively. N-methylpyrrolidone (NMP) was added and ground to prepare a slurry with a solid content of 61 wt%. The slurry was then coated (the areal density after drying was 13.9 mg / cm³). 2 A positive electrode sheet was fabricated on an aluminum foil current collector by drying, rolling, and cutting. A lithium metal sheet was used as the counter electrode, and a 1 mol / L LiPF6 solution of ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio 1:1) was used as the electrolyte. A Celgard 2400 polypropylene microporous membrane was used as the separator. A CR2032 coin cell was assembled in an argon-filled glove box. Charge-discharge tests were conducted at a rate of 0.1C within a voltage range of 2.8–4.3V, recording the initial discharge capacity and initial coulombic efficiency. A 200-cycle charge-discharge test was conducted at a rate of 1C, recording the capacity retention. The test results are shown in Table 1 and [Table data missing]. Figure 1 .

[0066] The surface residual alkali content (LiOH and Li2CO3) and electrochemical performance test results of the high-nickel cathode materials prepared in Examples 1-5 and Comparative Examples 1-3 are shown in Table 1.

[0067] Table 1. Test results of residual alkali and electrochemical performance of high-nickel cathode materials in Examples 1-5 and Comparative Examples 1-3.

[0068] As shown in Table 1, Examples 1 to 5 of the present invention have achieved effective removal of residual alkali on the surface of high-nickel cathode materials and significant improvement in electrochemical performance. The residual alkali (total amount of LiOH and Li2CO3) on the surface of high-nickel cathode materials has been reduced to below 500ppm, the initial discharge capacity is not less than 215.8mAh / g, the initial coulombic efficiency is not less than 90.1%, and the 1C / 200 cycle retention rate is not less than 89.3%.

[0069] Comparative Example 1, using traditional pure water washing, showed a high residual LiOH content of 913 ppm on the surface of the high-nickel cathode material, resulting in an initial discharge capacity of only 206.3 mAh / g, an initial coulombic efficiency of only 85.2%, and a 1C / 200-cycle retention rate of only 85.7%. Comparative Example 2, with a washing solution free of H2O2, showed a residual LiOH content of 609 ppm on the surface of the high-nickel cathode material, an initial discharge capacity of 210.5 mAh / g, an initial coulombic efficiency of 86.5%, and a 1C / 200-cycle retention rate of 87.3%. Comparative Example 3, with a washing solution free of NH4, showed a different result. + The high-nickel cathode material has a surface residual alkali LiOH content of 643 ppm, an initial discharge capacity of 209.8 mAh / g, an initial coulombic efficiency of 86.2%, and a 1C / 200-cycle retention rate of 86.5%. Comparative analysis of Comparative Examples 2 and 3 shows that using NH4 alone... + Neither salt nor H2O2 can fully remove residual alkali from the surface of high-nickel cathode materials and comprehensively improve their electrochemical performance. The synergistic effect of the two is crucial for the surface reconstruction and performance optimization of high-nickel cathode materials.

[0070] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a high-nickel cathode material with water-washed induced surface reconstruction, characterized in that, Includes the following steps: Water washing: The sintered high-nickel cathode material is dispersed in a water washing solution for water washing; wherein the water washing solution contains NH4. + Salt and H2O2, and the pH value of the washing solution is 7.5~10.5; Solid-liquid separation: After water washing, solid-liquid separation is performed to collect the solid material; Drying: The process of drying the collected solid materials; Heat treatment: The dried material is heat treated at 300℃~600℃ in an oxygen atmosphere.

2. The preparation method according to claim 1, characterized in that, The pH value of the washing solution is 8.5~9.5; And / or, the temperature of the heat treatment is 400℃~500℃.

3. The preparation method according to claim 1, characterized in that, The NH4 + Salts include at least one of ammonium chloride, ammonium nitrate, and ammonium sulfate; And / or, the washing solution contains NH4 + The salt concentration is 0.01 mol / L to 0.5 mol / L, preferably 0.05 mol / L to 0.2 mol / L; And / or, the mass fraction of H2O2 in the washing solution is 0.1% to 5%, preferably 0.5% to 2%.

4. The preparation method according to claim 1, characterized in that, The washing solution also contains a pH buffer; optionally, the pH buffer includes ammonia or an NH4Cl-NH3·H2O buffer solution. And / or, the washing solution is prepared by heating deionized water to 25°C~60°C and adding NH4. + Salt and H2O2 are stirred evenly to obtain the washing solution; optionally, the washing solution is prepared by heating deionized water to 35~45℃ and adding NH4+. + Salt and H2O2 are stirred evenly to obtain the washing solution.

5. The preparation method according to claim 1, characterized in that, The chemical formula of the sintered high-nickel cathode material is LiNi. x Co y M 1-x-y O2, where 0.80≤x≤0.98, 0<y<0.20, and x+y<1, and M is Mn and / or Al.

6. The preparation method according to claim 1, characterized in that, The solid-liquid ratio of the sintered high-nickel cathode material to the washing solution is 1:(1~10)g / mL, preferably 1:(2~4)g / mL; And / or, the stirring speed during the water washing process is 100rpm~800rpm, preferably 300rpm~500rpm.

7. The preparation method according to claim 1, characterized in that, The temperature of the water washing treatment is 10℃~50℃, preferably 25℃~40℃; And / or, the water washing treatment time is 1 min to 30 min, preferably 3 min to 15 min.

8. The preparation method according to claim 1 or 2, characterized in that, The drying process is vacuum drying at 80℃~150℃ for 2h~12h, preferably vacuum drying at 100℃~120℃ for 6h~10h; And / or, the heat treatment holding time is 2h to 10h, preferably 4h to 8h; And / or, after the heat treatment is completed, the furnace is cooled to room temperature and then sieved.

9. A high-nickel cathode material with water-wash-induced surface reconstruction, characterized in that, It is prepared by the method for preparing high-nickel cathode material with water washing-induced surface reconstruction as described in any one of claims 1 to 8.

10. The application of the high-nickel cathode material with water-washed induced surface reconstruction as described in claim 9 in the preparation of lithium-ion battery cathode sheets.